1970
DOI: 10.1530/jrf.0.0210267
|View full text |Cite
|
Sign up to set email alerts
|

Male Antifertility Compounds: Biological Properties of U-5897 and U-15,646

Abstract: Summary. Chlorohydrins U-5897 (3-chloro-1,2-propanediol) and U-15,646 (1,1\m='\-(pentamethylenedioxy) bis [3-chloro-2-propanol]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
42
1

Year Published

1970
1970
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(48 citation statements)
references
References 5 publications
5
42
1
Order By: Relevance
“…The concentrations of sodium, potassium, acid phosphatase, alkaline phosphatase and GPC were not altered. a-Chlorohydrin and epididymal plasma composition (Coppola, 1969;Samojlik & Chang, 1970), the guinea-pig (Ericsson & Baker, 1970), the monkey (Kirton et al, 1970), the ram (Kreider & Dutt, 1970), the boar (Johnson & Pursel, 1972) and the hamster (Lubicz-Nawrocki & Chang, 1974), but is apparently without action in the mouse and rabbit (Ericsson, 1970 The results of the present study amplify the previous report (Ericsson, 1970) that -chlorohydrin is without action in the rabbit. Also, in agreement with Turner (1971), 8 mg/kg/3 days would seem to be about the minimum antifertility regimen in the rat.…”
Section: Methodssupporting
confidence: 83%
See 1 more Smart Citation
“…The concentrations of sodium, potassium, acid phosphatase, alkaline phosphatase and GPC were not altered. a-Chlorohydrin and epididymal plasma composition (Coppola, 1969;Samojlik & Chang, 1970), the guinea-pig (Ericsson & Baker, 1970), the monkey (Kirton et al, 1970), the ram (Kreider & Dutt, 1970), the boar (Johnson & Pursel, 1972) and the hamster (Lubicz-Nawrocki & Chang, 1974), but is apparently without action in the mouse and rabbit (Ericsson, 1970 The results of the present study amplify the previous report (Ericsson, 1970) that -chlorohydrin is without action in the rabbit. Also, in agreement with Turner (1971), 8 mg/kg/3 days would seem to be about the minimum antifertility regimen in the rat.…”
Section: Methodssupporting
confidence: 83%
“…Ericsson & Baker (1970) were unable to detect any change in motility of either uterine or epididymal spermatozoa in rats given an antifertility dose of a-chlorohydrin. Other workers have observed an inhibitory effect of a-chlorohydrin on the motility of spermatozoa in the rat (Samojlik & Chang, 1970;Vickery et al, 1974), the ram (Kreider & Dutt, 1970;Brown & White, 1973) and the boar (Johnson & Pursel, 1972), and this has been contributory evidence for some workers (Johnson & Pursel, 1972;Brown & White, 1973) to suggest a direct effect of a-chlorohydrin on epididymal spermatozoa.…”
Section: Introductionmentioning
confidence: 78%
“…daily doses of 35 mg/kg body weight, or one 45 mg/kg dose, orally or subcutaneously, spermatocoeles and sperm granulomata occur (Ericsson 1970;Ericsson and Baker 1970). However, there was no histological evidence of such a lesion in the epididymis of the rams in these experiments.…”
Section: Discussionmentioning
confidence: 61%
“…The fact that U-5897 produces temporary or permanent sterility in the male rat, only temporary sterility in the guinea-pig and monkey (Ericsson & Baker, 1970;Kirton et al, 1970) (Mason & Young, 1967). It is suggested that the cadmium ion affects either the testicular vessels and their epididymal branches (Gunn, Gould, & Anderson, 1963), or their end-arterial capillary bed (Mason, Brown, Young & Nesbit, 1964).…”
Section: Discussionmentioning
confidence: 99%